Deep shadow [compact disc, unabridged] - White, Randy Wayne (White, Randy Wayne. Doc Ford series., 2010)
During a dive in a remote Florida lake, the rim of a cave collapses, trapping two of Doc Ford's friends. Ford himself manages to escape, only to surface and find two men waiting for him on the shore. Murderers and ex-cons, the men are intent on diving to the bottom of the very deep lake and uncovering the remains of a legendary plane wreck there, supposedly loaded with Cuban treasury gold. Ford's expertise is just what they need.